4(3x+6)-6(4x-7)=10x+3(4x-9)

Simple and best practice solution for 4(3x+6)-6(4x-7)=10x+3(4x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+6)-6(4x-7)=10x+3(4x-9) equation:



4(3x+6)-6(4x-7)=10x+3(4x-9)
We move all terms to the left:
4(3x+6)-6(4x-7)-(10x+3(4x-9))=0
We multiply parentheses
12x-24x-(10x+3(4x-9))+24+42=0
We calculate terms in parentheses: -(10x+3(4x-9)), so:
10x+3(4x-9)
We multiply parentheses
10x+12x-27
We add all the numbers together, and all the variables
22x-27
Back to the equation:
-(22x-27)
We add all the numbers together, and all the variables
-12x-(22x-27)+66=0
We get rid of parentheses
-12x-22x+27+66=0
We add all the numbers together, and all the variables
-34x+93=0
We move all terms containing x to the left, all other terms to the right
-34x=-93
x=-93/-34
x=2+25/34

See similar equations:

| 20Xn=7000 | | X/4=20;x=5 | | y=-4-3+3 | | 20Xx=7000 | | 8/9=7/3x | | -4x+33+2x+81=135 | | 8x+2+4x+11=121 | | 54=6x-36 | | ^+6x=16 | | 3x-37=48 | | 3(7-1)+2(y+3=13 | | 2x+14.5=25.5 | | 6/4x+3/4=2 | | 24=4(4m-2) | | 11y/28-2=4-7y/4 | | 2.2(4p+2=13.2 | | -3x=12-5+11 | | -9g=-0.74-16.4g | | 25v+3(5v+3)-4(7v+1)=-88 | | 29x+-3=15x+7 | | X+3+8=2x+4 | | (4)/(3)=(x)/(56) | | -8-15-18k=-11k+19 | | 1/5(n-10)=6-3.5 | | 4x+10+x+20=30 | | |8x-5|=-21 | | 2x+15.5=24.5 | | 4❨2x-3)=5x-42-2x | | 2x+0+x=180 | | -4-9b=-8b+14 | | 3x+7=5x=2(3-x)+1 | | 3(60-y/3)+y=180 |

Equations solver categories